PERANAN AGRO INDUSTRI DALAM PEMBANGUNAN INDUSTRI PEDESAAN - sutawi, sutawi (Jurnal Bestari, 1994)
Related to the national development, rural industrialization must be capable of playing its role as a part of agrarian and rural economy transformation. So that it will change gradually into industrial economy. Hence, as a matter of fact, the role and potential of farm-industry as the main activator of the rural Industrialization through its capability of motivating the growth and as a part of the rural economy transformation. And to reach that goal, the additional values from the farm-industry must be created.